Principal's Leadership Strategy in Developing the Quality of Teacher Resources - Muhamad Ali Anwar (Al-Hayat: Journal of Islamic Education, 2022)
Miftahul Huda Keringan Nganjuk Islamic Elementary School (SDI) is a favourite school in the Nganjuk district which has very encouraging achievements, and many are obtained from qualified teachers. Quality teachers cannot be separated from the principal's leadership strategy in developing teacher resources in the school. The method carried out by the principal is to develop teaching resources. This study aimed to explain the principal's strategy in developing teacher resources at SDI Miftahul Huda. This study uses an interpretive paradigm through a qualitative approach, the type of case study. Data was obtained from the principal directly as well as teachers and students. Data collection techniques using in-depth interviews, observation and documentation. Miles and Huberman's qualitative analysis model data analysis data reduction, data display and verification. They check the data's validity using triangulation; credibility, transferability, depandibility and confirmability. The study results show that various forms of the principal's strategy participate in multiple activities such as workshops, training and comparative studies at the national and international levels. The principal is the key to the school's success in carrying out development. So that activities to improve and improve programs in schools mainly lie with the principal himself.